Answered

Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Solve for n.

–2(n + 2) + 6 = 8

n =


Sagot :

Answer:

n = -3

Step-by-step explanation:

View image vikkbb101

Answer:

n = -3

Step-by-step explanation:

We have the equation –2(n + 2) + 6 = 8. First, we simplify it:

–2(n + 2) + 6 = 8

–2(n + 2) = -2n + (-4) = -2n - 4

So now we have:

-2n - 4 + 6 = 8

We can subtract 6 from both sides of the equation to get:

-2n - 4 = 2

We can also add 4 to both sides to get:

-2n = 6

Divide both sides by 2 to get:

-n = 3

Multiply both sides by -1 to get:

n = -3

Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.